2021
DOI: 10.1080/09638288.2020.1862314
|View full text |Cite
|
Sign up to set email alerts
|

Juggling the management of everyday life activities in persons living with chronic obstructive pulmonary disease

Abstract: Juggling the management of everyday life activities in persons living with chronic obstructive pulmonary disease, Disability and Rehabilitation,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…This finding is consistent with previous research on cognitive impairment in COPD, which reported that one-third of individuals with COPD and SCD-related limitations sought help from family and friends, and two-thirds required assistance with ADLs [ 16 ]. Reliance on assistance from family and friends may lead to frustration about their dependence on others [ 32 ]. In the absence of support from others, many individuals with COPD take frequent breaks while dressing or moving to accommodate their functional limitations, ultimately leading to the abandonment of day-to-day activities [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is consistent with previous research on cognitive impairment in COPD, which reported that one-third of individuals with COPD and SCD-related limitations sought help from family and friends, and two-thirds required assistance with ADLs [ 16 ]. Reliance on assistance from family and friends may lead to frustration about their dependence on others [ 32 ]. In the absence of support from others, many individuals with COPD take frequent breaks while dressing or moving to accommodate their functional limitations, ultimately leading to the abandonment of day-to-day activities [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Reliance on assistance from family and friends may lead to frustration about their dependence on others [ 32 ]. In the absence of support from others, many individuals with COPD take frequent breaks while dressing or moving to accommodate their functional limitations, ultimately leading to the abandonment of day-to-day activities [ 32 ]. Therefore, it is crucial to determine what increases the prevalence of SCD-induced functional limitations and establish care coordination practices to help reduce the burden they place on patients with COPD and their informal caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…As COPD progresses, individuals experience numerous symptoms, of which dyspnea, fatigue and muscle weakness are the most severe [ 17 , 21 ]. This consequently affects their ability to complete both daily life activities, such as dressing, stair climbing and household chores, and more complex tasks known as instrumental activities of daily living, such as shopping, housework and using public transport and individuals suffering from COPD face a difficult process of adaptation to their health condition [ 22 ]. Even though a number of studies have pointed out that the most widely recognized conditions causing functional limitations among people are rheumatoid arthritis, spine issues and cardiovascular disease and that these conditions increase in prevalence as the population ages [ 23 , 24 ], Djibo et al [ 25 ] reported that the highest rates of functional limitation occur in middle-aged adults (45–64 years old) with COPD, although the reasons for this finding are not completely understood.…”
Section: Introductionmentioning
confidence: 99%